Prevalence of mental disorders among depressed coronary patients with and without Type D personality: results of the multi-center SPIRR-CAD trial - Lambertus, Frank; Jünger, Jana; Schultz, Jobst-Hendrik (General hospital psychiatry, 2018)
Objective: Type D personality, as with formal mental disorders, is linked to increased mortality in coronary heart disease (CHD). Our aim was to determine the prevalence of mental disorders among depressed CHD patients with and without Type D personality. Methods: Depressive symptoms (HADS, HAM-D), Type D personality (DS-14) and mental disorders based on DSM-IV (SCID I and II) were assessed. Results were calculated by Kruskal-Wallis tests, Fisher's exact tests and logistic regression analyses. Results: 570 CHD patients were included (age 59.2±9.5years; male 78.9%, HADS-D depression 10.4±2.5; HAM-D 11.3±6.6; Type D 60.1%). 84.8% of patients with Type D personality and 79.3% of non-Type D patients suffered from at least one mental disorder (p=0.092), while 41.8% of Type D positives and 27.8% of Type D negatives had at least two mental disorders (p=0.001). Patients with Type D personality significantly more often had social phobia [odds ratio (95% confidence interval): 3.79 (1.1 to 13.12); p=0.035], dysthymia [1.78 (1.12 to 2.84); p=0.015], compulsive [2.25 (1.04 to 4.86); p=0.038] or avoidant [8.95 (2.08 to 38.49); p=0.003] personality disorder. Conclusions: Type D personality among depressed CHD patients is associated with more complex and enduring mental disorders. This implies higher treatment demands. Trial registration ISRCTN 76240576; NCT00705965